Blurring interspecific boundaries: antropocentrismo e discorso controegemonico nelle vignette umoristiche di Charles Schultz, Gary Larson e Dan Piraro - Elena dell’Agnese (Storia delle Donne)
According to the Western tradition, a “great divide” separates human beings from non-human animals. Such a boundary underlies the anthropocentric interpretation of the world and the power system that ecofeminists call ‘anthroparchy’. Given its capacity to break the rules, it is possible to assume that humour can undermine this hegemonic vision. To test such a hypothesis, the article examines the work of three American cartoonists who, albeit with different techniques and strategies, open a crack in this direction: Charles M. Schulz (Peanuts), Gary Larson (The Far Side) and Dan Piraro (Bizarro).